The Impact of Job Stress, Organizational Culture, Work Motivation on Turnover Intention of Pramusapa Employees - Gea, Fifi Jayanti; Novialumi, Anita (Reviu Akuntansi, Manajemen, dan Bisnis, 2025)
Purpose: This study aims to investigate the relationship between employee turnover intention in the service industry, namely PT Putratama Satya Bhakti, and job stress, organisational culture, and work motivation. Methodology: This study was carried out at the outsourced services provider PT Putratama Satya Bhakti. A standardised questionnaire disseminated via Google Forms was used to gather quantitative data from 85 employees. SPSS version 29, which includes multiple linear regression analysis and validity and reliability evaluations, was used to do the analysis. Results: The study found that work stress significantly increases turnover intention, while a positive organizational culture reduces it. Work motivation also shows a significant positive relationship with turnover intention, indicating that motivated employees may still consider leaving if their expectations are unmet. Conclusion: Partially, work stress has a significant and positive effect on turnover intention of pramusapa employees, organizational culture has a significant and negative effect on turnover intention of pramusapa employees, work motivation has a significant and positive effect on turnover intention of pramusapa employees. Simultaneously, the three variables have a significant effect on turnover intention. Limitations: The study's reliance on self-reported data from one organization is one of its limitations; it may not fully capture the dynamics of turnover intention in other sectors or businesses. Contribution: Theoretically, this study enriches the literature on psychological and organizational factors that influence turnover intention. Practically, the results provide input for HR practitioners and organizational leaders in designing effective retention strategies, especially in the service industry.